Synopsis: Cost effective options for inclusive and sustainable development in Rwanda - Aragie, Emerta A.; Niyonsingiza, Josue; Thurlow, James; Warner, James; Xu, Valencia Wenqian (International Food Policy Research Institute, 2025)
The study systematically ranks investment options in the agrifood system based on their cost-effectiveness across multiple development outcomes. Investments in SME processors and traders and livestock extension are the most cost-effective for promoting agrifood GDP growth and employment. SMEs and livestock services together with seed systems and credit access contribute positively to social outcomes (poverty, undernourishment, and diet). The analysis finds a trade-off between economic gains and environmental outcomes— higher GDP effects often come with greater environmental costs. The Rwandan case demonstrates a slight shift in the relative cost-effectiveness of investments when accounting for historical climatic risks. The study emphasizes the need for data-driven investment planning, climate-aware policies, and balancing short-term gains with long-term sustainability objectives.